Effects of Adult Feeding Treatments on Longevity and Egg Maturation in Non-Ovipositing Broomrape Females, Phytomyza Orobanchia Kalt (Diptera: Agromyzidae) - Hegazi, Esmat; Khafagi, Wedad; El-Rahman, Safaa Abd; Hasaneen, Mervat; Showiel, Sania; Shal, Amany Abou; El Eryan, Mohamed; Attia, Manal (European Journal of Applied Sciences, 2024)
Orobanchaceae, is noxious root parasites, in Egypt. Some causing huge economic losses to faba bean fields. So far, there are few detailed reports on the rearing protocols of its biological control agent, Phytomyza Orobanchia Kalt. The effect of food supplements on longevity and egg load in non-ovipositing Broomrape fly Ph.Orobanchia ,is not well known. We investigated the effect of three feeding regimes of the adult flies (supplement with sterile water or honey solution and starvation) on its longevity, and egg load female fly. Adult longevity was affected by feeding treatments, insect sex and hatching time. Under starvation, the longevity and egg load of Ph. Orobanchia adults were significantly lower than those with access to sterile water and a honey solution. Honey fed females of non diapaused flies lived longer than diapaused ones. Egg loads were significantly influenced by female age, feeding treatments and physiological state of the female. Females emerged without mature eggs. For honey solution fed flies, egg load increased until age of 3 d old (non-diapausing females) day 14 (diapausing females), reaching respective maxima of 28.2± 1.2 and 16.4 ± 2.2 eggs/female. Eggs load then declined with age. Non- diapausing females produce more eggs than diapausing ones.